A meta-analysis of the effectiveness and safety of microvascular decompression in elderly patients with trigeminal neuralgia. (May 2022) - Sun, Junwei; Wang, Mingyu; Zhang, Li; Yu, Yanbing
Highlights: BNI score allows comparison of different studies to be more feasible. Updated studies included makes the results more convincing. MVD is an effective and safe treatment in the elderly patient population. Abstract: Background: Microvascular decompression (MVD) has been increasingly performed in elderly patients with trigeminal neuralgia (TN). We conducted a meta-analysis to compare the effectiveness and safety of MVD in elderly and young patients with TN. Methods: Databases such as PubMed, EMBASE, and Cochran Library were utilized to collect relevant literatures prior to February 2020. Two researchers independently screened the literature, extracted the data, and evaluated the quality. Finally, the review manager software was used to conduct meta-analysis. Results: Overall, 12 studies were included in this analysis. The immediate efficacy, long-term efficacy, and complication rate of 681 elderly patients and 1538 young patients were compared after MVD. Results indicated that there were no significant differences in immediate postoperative effects between elderly and younger patients (92.7%: 90.1%, P = 0.13), while the postoperative long-term efficacy of elderly patients were significantly better than young patients (77.5%: 71.2 %, P = 0.04). There were no significant differences in the incidence of intracranial hemorrhage, bacterial meningitis, cerebrospinal fluid leakage, facial hypoesthesia, hearing impairment, and facial paralysis between the two age groups. Conclusion: MVD is an effective and safe treatment in the elderly patient population. Older patients tend to achieve better long-term results and advanced age should not be a contraindication for MVD treating TN.